Realitas Penyebaran Agama oleh Kaum Puritan - Musa, Dahniar Th. (Jurnal Pelangi Ilmu, 2008)
The study discusses Puritans migration process and religious intoleransce toward people of different divinity in Amerika sociaty, particularuy in the 19 and 20(/h century. This study employs library research in which the data were gathered from some sources: books, journals, novels, films, and internet. Besides, this study was conducted under interdisciplinary approach such as historical, cultural, sosiological, and micro to macro. The result of this study shows that the migration of Puritan society occures because they opposed absolute power of government and chruch. Having settled in Massachusetts, Amerika in order to find the religious freedom, the Puritan started to exploit otherś religious freedom. Thus, the Puritan democracy left in paradox. Hawthorne and Miller criticized the Puritan through their literary work. The Puritan huntet, exiled, executed people who did not have same belief as they were. This kinds of ethic were against Americanś democracy, equality, andfreedom as written in the Declaration of Independence. Hawthorne dan Miller also interpreted that religious behavior, everyone has a different belief although itś in the same religion. Thus, the Puritan intolerance indicated the tyranny behavior in the states which appreciated democracy and freedom for human being as a goods creation